The Role of Potentiality in Aristotle's Ethics. (May 2022) - Blumenfeld, Jacob
What I will argue here is that the ethical potentiality of the human being that Aristotle cites in the Nicomachean Ethics refers to the general, rational capacity for someone to appropriate and develop their own specific, natural capacities which make them human; the name of this ability is called virtue, which, when expressed in actions, we call good. To separate out the concepts at work here demands an exegesis of the two kinds of dunamis in Metaphysics Theta, that is, dunamis as causal power of change and dunamis as a potential way of being for an existent capacity. Once we grasp this, we can clarify the nature of virtue as the active, complete state of a capacity in human being which defines their function even though it must be acquired, and it need not ever be actualized. The concepts of habit ( ethos ) and practical judgment ( phronesis ) give Aristotle the means to solve the problem of how such a potentiality is acquired and how it is actualized, and hence we will end with a discussion of them.